Strategic localization of heart mitochondrial NOS: A review of the evidence - Zaobornyj, Tamara (2012)
Heart mitochondria play a central role in cell energy provision and in signaling. Nitric oxide (NO) is a free radical with primary regulatory functions in the heart and involved in a broad array of key processes in cardiac metabolism. Specific NO synthase (NOS) isoforms are confined to distinct locations in cardiomyocytes. The present article reviews the chemical reactions through which NO interacts with biomolecules and exerts some of its crucial roles. Specifically, the article discusses the reactions of NO with mitochondrial targets and the subcellular localization of NOS within the myocardium and analyzes the available data about heart mitochondrial NOS activity and identity. The article also describes the regulation of heart mtNOS by the distinctive mitochondrial environment by showing the effects of Ca2+, O2, L-arginine, mitochondrial transmembrane potential, and the metabolic states on heart mitochondrial NO production. The article depicts the effects of NO on heart function and highlights the relevance of NO production within mitochondria. Finally, the evidence on the functional implications of heart mitochondrial NOS is delineated with emphasis on chronic hypoxia and ischemia-reperfusion studies.